Medical applications of shape memory alloys - Machado,L.G. (2003)
Shape memory alloys (SMA) are materials that have the ability to return to a former shape when subjected to an appropriate thermomechanical procedure. Pseudoelastic and shape memory effects are some of the behaviors presented by these alloys. The unique properties concerning these alloys have encouraged many investigators to look for applications of SMA in different fields of human knowledge. The purpose of this review article is to present a brief discussion of the thermomechanical behavior of SMA and to describe their most promising applications in the biomedical area. These include cardiovascular and orthopedic uses, and surgical instruments.